Exploring Nurses’ Documentation of their Contribution to Traumatic Brain Injury Rehabilitation in an Aotearoa-New Zealand Rehabilitation Unit - Davenport, Angela C. (Auckland University of Technology, 2020)
This thesis explores how a group of Aotearoa-New Zealand rehabilitation nurses documented their contribution for clients with traumatic brain injury and the influences on that documentation. A critical realist case study framework was utilised. In acknowledging critical realist principles of a layered reality, the research involved three phases. • Phase A incorporated environmental description, and a questionnaire completed by two managers; • Phase B involved an audit of nurses’ documentation from their routine records and from the clients’ timetables; and, • In Phase C, nurses were interviewed to seek their perspective of their contribution and the documentation choices they made. Preliminary themes arising from Phase A and trends from the nurses’ documentation patterns (identified in Phase B) were discussed with the nurses in Phase C. Findings indicated that there were differences in the way nursing worked in the facility, relating to the environment, and a differentiation in contractual expectations of nurses compared to their allied health colleagues. Enablers and constraints to documentation practice were highlighted. It was apparent that many nurses viewed their role in rehabilitation differently. Their perceptions of their role, facility norms, and standardisation of documentation practice influenced how and what they chose to record in their daily records. To further explore how nurses documentation was produced and shaped by underlying structures and powers, I applied Archer’s (1995) morphogenetic analytical framework. This framework was adopted as it recognises that a person’s context are the effects of past actions of others, meaning that they function in conditions they themselves have not chosen. However, it also recognises human agency, and the ability to change or transform. Archer’s framework provided insights into structural and cultural properties that shaped nurses’ documentation. It unearthed complexity in nurses’ decision making regarding what they chose to document of their practice. Individual patterns of working were identified, which led to individual understandings of documentation expectations and practice. Even though nurses collectively had the potential to reflect upon and change their documentation practice, there was little evidence of them influencing the social or cultural structures within the facility. The implications for rehabilitation are given in the form of six major recommendations. These encompass organisational level decision-making and the practice of individual nurses, and include: 1) Modifying the induction processes relating to documentation; 2) Provision of structures and forums to enhance nurses’ collective voice; 3) A review of the way nurses’ documentation supports communication; 4) Establishing ongoing education to the nursing team from a senior nurse knowledgeable in rehabilitation nursing documentation requirements; 5) Endorsing an integrated model of rehabilitation nursing that supports understanding of the way all nursing interventions contribute to rehabilitation; and, 6) Articulating a shared language structure to consistently describe nursing interventions. The findings highlight the specialty practice of rehabilitation nursing and give insights into nurses’ documentation of their rehabilitation contribution. By generating discussion and momentum, and providing options to advance unity and teamwork, this should ultimately benefit peoples’ rehabilitation journeys.
Keywords: Rehabilitation nursing; Documentation; Traumatic brain injury; Nursing contribution